Thin Film Processes - Jung, Hyun Wook (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Thin film processes are significantly incorporated in manufacturing display panels, secondary batteries, fuel/solar cells, catalytic films, membranes, adhesives, and other commodity films. This Special Issue on "Thin Film Processes" of Processes listed recent progress on thin-film processes, covering theoretical considerations, experimental observations, and computational techniques. Articles in this Issue consider comprehensive studies on thin film processes and related materials.